Profile of patients presenting at a low vision clinic in a developing country - Olusanya, Bolutife (BioMed Central, 2012)
BACKGROUND: Low vision is an important public health problem; however, very few low vision clinics are available to address the needs of low vision patients in most developing countries. The purpose of this study was to describe the characteristics of patients attending the low vision clinic of a Nigerian tertiary hospital. METHODS: This was a prospective cross sectional study of all new patients seen at the low vision clinic over a 36 month period. Patients were administered with a structured questionnaire, and were examined and tested with low vision devices by the attending low vision specialist. Information on the demographic and clinical characteristics of the patients was recorded. RESULTS: A total of 193 new patients seen during the period were studied. The mean age was 41.4 years, and their ages ranged between 6 and 90 years with a male to female ratio of 1.9:1. Majority (58%) were aged below 50 years, 23.3% were children (≤15 years), while 21.8% were elderly patients (≥65 years). The commonest cause of low vision was retinitis pigmentosa (16.6%); 14.5% had age related macular degeneration (ARMD); 9.8% had albinism; while only 1% had diabetic retinopathy. ARMD (45.2%) was the commonest cause in the elderly patients, while albinism (24.4%) and optic atrophy (24.4%) were the commonest in children. CONCLUSION: The demographic and clinical characteristics of low vision patients seen in this clinic are similar to that of patients in other developing countries, but different from those in developed countries. Elderly patients and females may be under-utilising low vision services. There is a need for further research into the determinants of low vision service utilisation in developing countries. This would further aid the planning and delivery of services to low vision patients in these countries.